Simultaneous two-team transorbital neuroendoscopic approach for sphenoid wing meningioma - Lien Deschuytere; Estelle Beneke; Byron De John; Darlene Lubbe (Journal of the Colleges of Medicine of South Africa)
Background: Surgery for skull base lesions is often time-consuming. In this research, we aimed to improve the efficiency of transorbital neuroendoscopic surgery (TONES) for skull base lesions, specifically sphenoid wing meningiomas, by reducing operative time without compromising patient safety or surgical outcomes.